ANALISIS PASAR AIR BERSIH DI PROVINSI BALI MENGGUNAKAN PARADIGMAN STRUCTURE-CONDUCT-PERFORMANCE (SCP): ANALISIS PASAR AIR BERSIH DI PROVINSI BALI MENGGUNAKAN PARADIGMAN STRUCTURE-CONDUCT-PERFORMANCE (SCP) - Dewa Bagus Trima Putra; I Wayan Sukadana (E-Jurnal Ekonomi Pembangunan, 2025)
Clean water availability is a fundamental human need that must be sustainably fulfilled. Bali Province, as a tourist destination, faces increasing clean water demand that is not matched by adequate distribution capabilities. This study aims to analyze the market structure, supplier behavior, and market performance of clean water providers in Bali using the Structure-Conduct-Performance (SCP) paradigm. A quantitative method was applied through market concentration measurement using the Herfindahl-Hirschman Index (HHI), supported by qualitative analysis to explore supplier behavior. Secondary data were sourced from Village Potential Survey (PODES) and the Central Statistics Agency. The results indicate that public sector dominance and high market concentration prevail across Bali. Supplier behavior shows limited responsiveness to local needs, while market performance is characterized by disparities in clean water access. Kernel regression indicates a negative relationship between market concentration and service coverage equity. This study suggests enhancing service diversification, increasing private and community sector involvement, and designing clean water management policies based on local needs.